A Study on Bead on Plate Welding of AA7075 By Low Power Fiber Laser - M., Ishak; M. N. M., Salleh; F. R. M., Romlay (2015)
AA7075 aluminium alloy has many advantages due to its light weight, low density, high corrosion resistance, and high strength metal. In order to have a strong weld joint, the weld penetration should be maximized, as well as the heat affected zone (HAZ) and weld width should be minimized. Laser welding method can produce the weld joint with these weld characteristics. Fiber laser welding process was known to be the best laser welding method among other laser welding processes such are YAG, CO2, and LD (diode) laser due to its power, high beam quality, and low cost maintenance. The important thing need to be considered for the laser welding is the focus point of the laser beam and the penetration depth. Bead-on-plate (BOP) welding was carried out by heating the surface of AA7075. The images of welded line were captured using an optical microscope and beam width was measured. The beam diameter of focus point is 570 µm at focal length of 120 mm. Penetration depth also was measured from the captured image of cross-section of BOP welded sample by optical microscope. Pulse wave (PW) welding mode process produced the optimum depth approximately 1.0 mm with keyhole penetration produced compared to continuous mode (CW) welding, which produced 0.153 mm penetration depth.